Penerapan Perilaku Hidup Bersih dan Sehat di Desa Parakanjaya - Ade Saputra Nasution (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Health protocol is a public health effort that refers to some actions that need to be taken in the context of health promotion and disease prevention. During the current pandemic, people are required to apply the Health Protocol in their daily life to break the chain of the spread of disease, such as the importance of wearing masks, washing hands with soap, and running water, carrying hand sanitizers, maintaining distance, eating nutritious food, diligently exercising. at home, don't shake hands first, use electronic money and when you get home, take a shower. The purpose of community service is to increase knowledge and awareness of the community, especially children and mothers regarding the importance of implementing new habits with the discipline of health protocols and increasing knowledge of PHBS. The method of community service activities in Salabenda Village, RT 03/03 in Parakanjaya Village, Kemang District, which is carried out is educating about increasing PHBS knowledge during the current pandemic. The results of this community service activity are that the Salabenda Village children can practice PHBS such as how to wash their hands properly and correctly and comply with Health protocols when there are activities.